The Role of Natural Resources in the Ecotourism Development – Residents’ Perceptions in Subotica (Northern Serbia) - Aleksandra Vujko; Marko D. Petrović; Danica Gostović; Milan Radovanović; Darko Vuković (DETUROPE)
Regardless of their type and structure, natural resources represent the basis for industrial and economic development of every country. The aim of this study is to determine and display the natural potential in the territory of the City of Subotica (Vojvodina Province in Northern Serbia), on the basis of four protected natural areas. These areas are: Palić Nature Park, Ludaško jezero Special Nature Reserve, Selevenjske pustare Special Nature Reserve and Subotička peščara Protected Landscape of Exceptional Distinction. All listed areas represent the main aspects for ecotourism development in this part of the country, so one of the aims of the research is to identify key stakeholders that should be involved in proper developing of this form of tourism. When preforming this study, survey research techniques were used. Respondents were Subotica’s residents, who were asked to rate the state of the environment in these surroundings, as well as to give their opinions about the possibilities for the development of ecotourism. Based on the analysis of the dependent and independent variables, it was concluded that the residents are generally satisfied with the conditions of the environment, they also consider that the development of this form of tourism would raise the awareness of locals about the importance of preserving these protected areas. The result may be significant when launching a new tourism product, while preserving the protected areas and adapting for future visitors’ needs.